Le développement durable dans la crise en Europe - Edwin Zaccai (Développement Durable et Territoires)
This paper analyses the situation of sustainable development in a European Union that is undergoing a severe economic crisis since 2008. First it describes the gap between the challenges put to the forefront in sustainable development discourses on the one side and the causes of this crisis on the other. In addition, the stress of public budgets under the crisis influence weakens the support for ecological and energy transitions, at a time when climate policies are already suffering of difficulties of their own. However, and this is examined in the second part of the paper, sustainable development objectives continue to be affirmed in European policy texts, including references to environmental limits to protect, and long term transition goals. In the third part we scrutinize the place of economic approaches in these policies. An ambiguity is shown between on the one side the preeminence of economic short term justifications for policy measures, and on the other side the idea that the stagnation of economic indicators could also sustain alternative indicators of well-being, indicators that have been promoted within sustainable development goals. We conclude by launching some ideas about the articulation of critics on ecological and economic failures.